Sex differences in the neural processing of aversive interoceptive events: the benefit of relief. - Giulia Galli; Akanksha Shukla; Alan N Simmons; Paul W Davenport; Martin P Paulus (PLoS ONE, 2013)
Do men and women process and experience unpleasant bodily states differently? We used fMRI to determine brain processing before, during and after an aversive respiratory stimulation. No sex difference emerged during anticipation or stimulation. However, after the offset of the stimulation, men but not women showed enhanced activation of brain regions that are important for interoception and reward processing. Moreover, this activation was highest in those males who rated the preceding stimulation as most unpleasant. These results indicate that men are particularly sensitive to reward associated with the termination of an aversive event, which may signal relief.